2005
DOI: 10.1158/1055-9965.epi-04-0759
|View full text |Cite
|
Sign up to set email alerts
|

Tissue-Specific Attenuation of Endogenous DNA I-Compounds in Rats by Carcinogen Azoxymethane: Possible Role of Dietary Fish Oil in Colon Cancer Prevention

Abstract: I-compounds are bulky covalent DNA modifications that are derived from metabolic intermediates of nutrients. Some

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0

Year Published

2006
2006
2015
2015

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 10 publications
(11 citation statements)
references
References 64 publications
0
11
0
Order By: Relevance
“…78 Fish oil reduces proliferation in upper-crypt cells of patients with a history of colonic polyps, 79 inhibits colon tumors, 80 in combination with fiber reduces aberrant crypt foci formation, 81 and has chemopreventive effects in colon cancer. 82 Whey suppresses angiogenesis and tumor development and induces apoptosis. 83 Shark cartilage is antiangiogenic, 84 although 1 human study found no benefits.…”
Section: Discussionmentioning
confidence: 99%
“…78 Fish oil reduces proliferation in upper-crypt cells of patients with a history of colonic polyps, 79 inhibits colon tumors, 80 in combination with fiber reduces aberrant crypt foci formation, 81 and has chemopreventive effects in colon cancer. 82 Whey suppresses angiogenesis and tumor development and induces apoptosis. 83 Shark cartilage is antiangiogenic, 84 although 1 human study found no benefits.…”
Section: Discussionmentioning
confidence: 99%
“…The fatty acid compositions of FO and CO are listed in Table 2. In order to meet essential fatty acid requirements, the FO diet contained 3.5 g of corn oil/100 g of diet [31], [32]. To prevent formation of oxidized lipids, the diet was stored at −20°C in the dark.…”
Section: Methodsmentioning
confidence: 99%
“…DNA extraction and 32 P-postlabeling analyses were performed as in previous experiments [32]. DNA was isolated by solvent extraction combined with enzymatic digestion of protein and RNA [26], [27] and stored at −80°C until analysis.…”
Section: Methodsmentioning
confidence: 99%
“…DNA extraction and 32 P-postlabeling analyses were performed as in previous experiments (Phillips and Arlt 2007; Zhou et al 2005). DNA was isolated by solvent extraction combined with enzymatic digestion of protein and RNA (Gupta 1984; Randerath et al 1981) and stored at –80°C until analysis.…”
Section: Methodsmentioning
confidence: 99%